Verbal Sexual Violence On X : A Gender Perspective and Digital Communication Ethics - Putri Regita Ramadhani; Laili Etika Rahmawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The development of social media has brought significant changes in people's communication patterns, but it has also become a vulnerable space for violence, including verbal sexual violence. This study aims to analyze the forms and characteristics of verbal sexual violence that appear on social media based on a gender perspective. Through a qualitative approach with a case study method, data was collected through content observation on various social media platforms, including comments, captions, and direct messages. The results show that verbal sexual violence tends to be experienced more by women, and is often excused as a joke or free expression of opinion. The inequality of gender-based power relations is the main factor that perpetuates this practice. In addition, weak digital ethics literacy exacerbates the situation, where perpetrators do not understand or ignore ethical boundaries in communicating online. This research emphasizes the importance of strengthening gender perspectives and digital communication ethics education as preventive efforts against verbal sexual violence in the digital space, particularly through institutional policies and community awareness programs.